다중오믹스 데이터를 위한 가중변수 스펙트럼 군집화 기법 - 이윤정(Yunjung Lee); 박세영(Seyoung Park) (Ŭngyong tʻonggye yŏnʼgu, 2023)
In recent years, high-throughput sequencing technologies generated rich resources of diverse types of omics data. Using the integration and analysis of multi-omics datasets, we can better understand cancer etiology and treatment responses. One of the important goals of multi-omics analysis in cancer research is to classify tumors by identifying subtypes of cancer patients. However, there are limitations to applying the existing clustering methods due to high dimensionality and heterogeneity of omics data. In this paper, we propose a new clustering method based on the spectral clustering algorithm, in which different weights are assigned to each omic and gene. The proposed optimization problem is non-convex, and clustering is performed through the iterative update process. The proposed clustering method performs better than the existing methods through simulation and real data application. 생물학적으로 각기 다른 부분 정보를 담고 있는 오믹스(omics) 데이터를 통합한 다중 오믹스(multi omics) 분석의 중요한 목표 중 하나는 암 타입의 하위 유형을 식별하는 것이다. 그러나 오믹스 데이터의 높은 차원과 이질성으로 인해 기존의 군집화 방법을 적용하는 데에는 한계가 있다. 본 논문에서는 대표적인 그래프 이론에 기반한 스펙트럼 군집화(spectral clustering) 방법론을 기반으로 새로운 알고리즘을 제안하고, 각 오믹스 데이터와 유전자 별로 가중치를 부여하는 것을 통해 중요 오믹스 데이터와 유전자를 식별 할 수 있다는 점에서 기존의 다중 오믹스 분석방법과의 차별점이 있다. 제안하는 방법의 알고리즘 최적화 식은 비볼록 최적화(non-convex optimization) 문제로, 반복적으로 업데이트하는 과정을 통해 군집화를 진행한다. 또한 시뮬레이션과 실데이터 적용을 통해 제안하는 군집화 방법이 기존의 다른 방법들보다 성능이 좋은 것을 확인 가능하다.